The Analysis, Design and Evaluation of an Unstructured Bra - Niemczyk, Lize (Auckland University of Technology, 2005)
This practice-based research focuses on the analysis, design and evaluation of an unstructured push-up plunge bra, which combines technical know-how with the sensitivity of bra wearers. The goal of such a dual combination was to create an easily wearable, yet extremely comfortable, fashionable and health-conscious bra. Current bra designs do not contribute to the well-being of the wearer and employ devices that substantially constrict the breasts with unhealthy results. The proposed exegesis introduces a new prototype bra based on new concepts and new construction techniques inspired by old bra patents, and on the latest design information captured from a variety of technological, material and process information. This exegesis documents an historical overview of bra design and the conceptualisation, design, prototyping and evaluation of six significant bra concepts. This project consists of an exhibition of practical work that represents the main body of applied research. The practical work constitutes 80% and the exegesis consists of 20% of the project’s value.
Keywords: Fashion development; Lingerie